The Behavior Of Customers Choice In Educational Institutions - Hasan Baharun; Mistria Harmonis; Amir Amir; Adi Wibowo; Shafa Maliya Fitriyah Sumarhum (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to analyze consumer behavior in making choices in educational institutions during the pandemic at MTs Nurul Jadid based on Islamic boarding schools. This research method uses a qualitative approach to the type of case study. This study shows that from the many differences in people's behavior in choosing a product/service, there has been a change in the current pandemic. The community's changes in behavior experienced by the community are caused by consumers feeling that government policies related to distance learning are no longer conducive to their children. Therefore, the public tends to prefer educational institutions that continue to carry out face-to-face learning during the pandemic. Based on the analysis and discussion, consumer behavior in choosing educational institutions during the pandemic is based on the following five things: Value Adde, Good Performing Image, Blended Learning Method's, Health Protocol Policy, and Repetitive Activities